Perancangan dan Pengembangan Aplikasi Profil Klub Berbasis Website Studi Kasus Fast Archery Pulomas - Kirana Maharani, Kirana Maharani; Kurniawati, Yulia Ery (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
This study aims to develop a web-based club profile application for the FAST Pulomas club. At present, the FAST Pulomas club does not yet have a portal that provides club information digitally, and the promotion process is still being carried out word-to-mouth. Therefore, this application was designed and developed to promote the club and create an official website to provide information about the club. The software development life cycle used the Rational Unified Process (RUP) with the Unified Model Language (UML) as the modeling system. Laravel used a framework in it’s development. The black box testing results show that all the application functionalities work as expected. And based on the user experience testing, it shows that the application provides positive results.